Anti-melanogenesis effect from Wampee fruit pectin via α-MSH/TRY pathway in A375 cells - Weiyu Fu; Xuehua Liao; Qian Zhang; Yuzhen Zhu; Si Mei; Qian Li; Xin Zhou; Xiaojun Li; Hui Luo; Hua Ye; Kefeng Wu (BMC, 2022)
Abstract Background Polysaccharides from wampee have been reported to process various biological activities, while the relationship between structure and bioactivities has been barely addressed. Pectin, an abundant water-soluble polysaccharide in wampee, showed significant antioxidant activity, which was associated with the anti-melanogenic activity. Therefore, this study investigated the physicochemical characteristics and the anti-melanogenesis effect of pectin extracted from wampee fruit in A375 cells. Methods The physicochemical characterization of pectin from wampee fruit was investigated by gel chromatography (GCP), FT-IR spectroscopy, and NMR spectroscopy methods. The anti-melanogenesis effects and mechanism were evaluated by mushroom tyrosine enzyme and human melanin cell model in vitro. Results The results showed that a molecular weight of 5.271 × 105 Da wampee fruit pectin (WFP) were mainly composed of mannose (Man), ribose (Rib), rhamnose (Rha), glucuronic acid (Glc A), glucose (Glc), galacturonic acid (Gal A), galactose (Gal), and arabinose (Ara), which linked with →4)-β-D-Galp-(1 → units. The current study revealed that WFP could significantly suppress mushroom TRY activity in vitro. Furtherly, WFP significantly reduced intracellular and extracellular melanin formation in A375 melanoma cells depending on the presence of alpha-melanocyte stimulating hormone (α-MSH). TRY activity was only inhibited in α-MSH treated A375 cells. Western blot analysis demonstrated that WFP reverse α-MSH induced melanogenesis in A375 melanoma cells, including in down-regulated TRY, TYRP-1, TYRP-2, MITF and CREB expressions. Conclusion These results indicated that WFP could inhibit α-MSH induced melanogenesis in A375 melanoma cells via α-MSH/TRY pathway. In conclusion, these data provided a new perspective to annotate WFP anti-melanogenesis activity mechanism.